Neuronal maturation and axon regeneration: unfixing circuitry to enable repair - Hilton, Brett J; Griffin, Jarred M; Fawcett, James W; Bradke, Frank (Nature reviews. Neuroscience, 2024)
Mammalian neurons lose the ability to regenerate their central nervous system axons as they mature during embryonic or early postnatal development. Neuronal maturation requires a transformation from a situation in which neuronal components grow and assemble to one in which these components are fixed and involved in the machinery for effective information transmission and computation. To regenerate after injury, neurons need to overcome this fixed state to reactivate their growth programme. A variety of intracellular processes involved in initiating or sustaining neuronal maturation, including the regulation of gene expression, cytoskeletal restructuring and shifts in intracellular trafficking, have been shown to prevent axon regeneration. Understanding these processes will contribute to the identification of targets to promote repair after injury or disease.
Keywords: Neurons; neurogeneze; zvířata; Humans; regenerace nervu; Neurogenesis; Nerve Regeneration; axony; neurony; lidé; Axons; Animals